Modulation of Tumor-Associated Macrophages (TAM) Phenotype by Platelet-Activating Factor (PAF) Receptor. (27th December 2017) - da Silva Junior, Ildefonso Alves; Stone, Simone Cardozo; Rossetti, Renata Marques; Jancar, Sonia; Lepique, Ana Paula
Abstract : Platelet-activating factor (PAF) plays an important role in the pathogenesis of several types of tumors. The biological effects of PAF are mediated by the PAF receptor (PAFR), which can be expressed by tumor cells and host cells that infiltrate the tumor microenvironment. In the present study, we investigated the role of PAFR expressed by leukocytes that infiltrate two types of tumors, one that expresses PAFR (TC-1 carcinoma) and another that does not express the receptor (B16F10 melanoma) implanted in mice that express the receptor or not (PAFR KO). It was found that both tumors grew significantly less in PAFR KO than in wild-type (WT) mice. Analysis of the leukocyte infiltration shown in PAFR KO increased the frequency of neutrophils (Gr1 + ) and of CD8 + lymphocytes in B16F10 tumors and of CD4 + lymphocytes in TC-1 tumors. PAFR KO also had a higher frequency of M1-like (CD11c + ) and lower M2-like (CD206 + ) macrophages infiltrated in both tumors. This was confirmed in macrophages isolated from the tumors that showed higher iNOS, lower arginase activity, and lower IL10 expression in PAFR KO tumors than WT mice. These data suggest that in the tumor microenvironment, endogenous PAF-like activity molecules bind PAFR in macrophages which acquire an M2-like profile and this promotes tumor growth.